Experience with German Research Consortia in the field of chemical biology of native nucleic acid modifications - Helm, Mark; Bohnsack, Markus; Carell, Thomas; Dalpke, Alexander; Entian, Karl-Dieter; Ehrenhofer-Murray, Ann; Ficner, Ralf; Hammann, Christian; Höbartner, Claudia; Jäschke, Andres; Jeltsch, Albert; Kaiser, Stefanie; et al. (ACS chemical biology, 2023)
The chemical biology of native nucleic acid modifications has seen an intense upswing, first concerning DNA modifications in the field of epigenetics and then concerning RNA modifications in a field that was correspondingly rebaptized epitranscriptomics by analogy. The German Research Foundation (DFG) has funded several consortia with a scientific focus in these fields, strengthening the traditionally well-developed nucleic acid chemistry community and inciting it to team up with colleagues from the life sciences and data science to tackle interdisciplinary challenges. This Perspective focuses on the genesis, scientific outcome, and downstream impact of the DFG priority program SPP1784 and offers insight into how it fecundated further consortia in the field. Pertinent research was funded from mid-2015 to 2022, including an extension related to the coronavirus pandemic. Despite being a detriment to research activity in general, the pandemic has resulted in tremendously boosted interest in the field of RNA and RNA modifications as a consequence of their widespread and successful use in vaccination campaigns against SARS-CoV-2. Funded principal investigators published over 250 pertinent papers with a very substantial impact on the field. The program also helped to redirect numerous laboratories toward this dynamic field. Finally, SPP1784 spawned initiatives for several funded consortia that continue to drive the fields of nucleic acid modification.